1998
DOI: 10.3133/fs00998
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient transport in the major rivers and streams of the Puget Sound Basin, Washington

Abstract: Each year, approximately 11,000 tons of inorganic nitrogen and 2,100 tons of total phosphorus are transported by rivers and streams to Puget Sound and its adjacent waters Rivers that have the largest streamflows carry the largest nutrient loads Nutrient yields are largest from basins with higher percentages of urban and agricultural areas and that receive the highest inputs of nutrients Why are nutrients important in the Puget Sound Basin?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Here, we likely omitted an important OM source, as evidenced by extremely high δ 15 N signatures during the low flow period. The Samish River has one of the highest nitrogen concentrations in the area, largely because the catchment area is dominated by agricultural land (Inkpen and Embry ), and is therefore influenced by artificial fertilizers and manure effluent with δ 15 N ranges between +2‰ and +30‰ (Lefebvre et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we likely omitted an important OM source, as evidenced by extremely high δ 15 N signatures during the low flow period. The Samish River has one of the highest nitrogen concentrations in the area, largely because the catchment area is dominated by agricultural land (Inkpen and Embry ), and is therefore influenced by artificial fertilizers and manure effluent with δ 15 N ranges between +2‰ and +30‰ (Lefebvre et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we likely omitted an important OM source, as evidenced by extremely high d 15 N signatures during the low flow period. The Samish River has one of the highest nitrogen concentrations in the area, largely because the catchment area is dominated by agricultural land (Inkpen and Embry 1998), and is therefore influenced by artificial fertilizers and manure effluent with d 15 N ranges between +2& and +30& ). The combination of a missed OM source and placement of the tripod likely drive the unexpected redundancy model relationships between maximum particle speeds, net range of particle transport, and marsh detritus.…”
Section: Comparing Consumers As Indicators Of Food Web Connectivitymentioning
confidence: 99%
“…Therefore, urban land use has a small P application rate (see Table 1) compared to that observed in literature (USE-PA, 1980). Atmospheric deposition of P for the Fishtrap Creek Catchment was assumed to be equivalent to that estimated for the whole Nooksack River basin (Inkpen and Embrey, 1998). Atmospheric deposition of P is included in P application rates of all land use categories.…”
Section: P Application Ratesmentioning
confidence: 99%
“…Land use pajerns also play an important role. Researchers have found that more agriculturally acKve and heavily urbanized watersheds contribute three Kmes the nitrogen and phosphorous loads to the Puget Sound than the forested watersheds in the Olympic Mountains (Inkpen and Embrey., 1998).…”
Section: Water Quality and Waste Processingmentioning
confidence: 99%